Photosensitizer‐Anchored 2D MOF Nanosheets as Highly Stable and Accessible Catalysts toward Artemisinin Production. Issue 11 (9th April 2019) - Wang, Ying; Feng, Liang; Pang, Jiandong; Li, Jialuo; Huang, Ning; Day, Gregory S.; Cheng, Lin; Drake, Hannah F.; Wang, Ye; Lollar, Christina; Qin, Junsheng; Gu, Zhiyuan; et al.
Abstract: 2D metal–organic frameworks (2D‐MOFs) have recently emerged as promising materials for gas separations, sensing, conduction, and catalysis. However, the stability of these 2D‐MOF catalysts and the tunability over catalytic environments are limited. Herein, it is demonstrated that 2D‐MOFs can act as stable and highly accessible catalyst supports by introducing more firmly anchored photosensitizers as bridging ligands. An ultrathin MOF nanosheet‐based material, Zr‐BTB (BTB = 1, 3, 5‐tris(4‐carboxyphenyl)benzene), is initially constructed by connecting Zr6 ‐clusters with the tritopic carboxylate linker. Surface modification of the Zr‐BTB structure was realized through the attachment of porphyrin‐based carboxylate ligands on the coordinatively unsaturated Zr metal sites in the MOF through strong Zr‐carboxylate bond formation. The functionalized MOF nanosheet, namely PCN‐134‐2D, acts as an efficient photocatalyst for 1 O2 generation and artemisinin production. Compared to the 3D analogue (PCN‐134‐3D), PCN‐134‐2D allows for fast reaction kinetics due to the enhanced accessibility of the catalytic sites within the structure and facile substrate diffusion. Additionally, PCN‐134(Ni)‐2D exhibits an exceptional yield of artemisinin, surpassing all reported homo‐ or heterogeneous photocatalysts for the artemisinin production. Abstract : It is demonstrated that 2D metal–organic frameworks can act as stable and highly accessible catalyst supports by introducing more firmly anchored photosensitizers as bridging ligands. Remarkably, PCN‐134(Ni)‐2D exhibits an exceptional yield of artemisinin, surpassing all reported homo‐ or heterogeneous photocatalysts for the artemisinin production.